Strategy for the Development of Patient Services at the YAPIDA Primary Clinic in Gunung Putri, Bogor Regency - Achmad Mustafa Kamal; Musa Hubeis; Mukhammad Najib (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
The change in the service system from the general customer category to the BPJS Health participant category resulted in a decrease in the number of visits by general participants and an increase in visits by BPJS Health participants. This research aims to formulate a strategy for the development of the Klinik Pratama YAPIDA, Gunung Putri, Kabupaten Bogor based on an analysis of patient service’s satisfaction. Research data was collected through a service quality questionnaire as developed, which consists of 5 (five) dimensions: tangible, reliability, responsiveness, assurance, and empathy. The data analysis technique uses a combination of Servqual analysis approach, Importance Performance Analysis (IPA) approach, and Structural Equation Model (SEM). The research’s result shows that based by the use of the combination of the three analytical approaches, there is a linearity in the strategic direction of the Klinik Pratama YAPIDA development to maintain sustainability and increase the grade of the Clinic, which is improving service quality in aspects of 1) Nurse’s responsiveness, 2) responsiveness of the pharmacist, and 3) clinical service officer. Based on this analysis, the managerial implications require the YAPIDA Primary Clinic Management to formulate a service quality development strategy by improving the three service attributes.